Predictive Design to Determine Optimal Absorber Placement in Colloidal Photonic Crystals - Bleyer, Gudrun; Nees, Nico; Prohaska, Florian; Pflug, Lukas; Stingl, Michael; Vogel, Nicolas (Advanced Optical Materials, 2025)
Structural coloration abounds in nature and its remarkable optical effects are mimicked in synthetic photonic crystals and glasses. However, the color saturation of these synthetic structures is often diminished by incoherent scattering caused by defects and irregularities. The inclusion of absorbing materials increases color saturation, but where this absorber is most efficiently incorporated within a photonic structure remains unknown. Here, this question is addressed using predictive design. A mathematical structure optimization algorithm is developed that iteratively places absorbing particles within a colloidal photonic crystal until an optimal distribution that produces maximum chroma values is identified. This rigorous optimization shows that placement of the absorbing material in the bottom layers of the photonic structure is most efficient in producing highly chromatic structural colors compared to other common absorber placements. Experiments based on a layer-by-layer assembly of polystyrene@polydopamine core–shell particles with controlled absorber distribution confirm these findings. These results demonstrate the ability of predictive design to guide the experimental realization of structurally-colored materials with optimal properties without the need for time- and resource-consuming experimental parameter studies.
CRIS-Team Scopus Importer:2025-02-14
Keywords: absorber; colloidal crystal; optimization; polydopamine; predictive design; structural color